Water quality. Biological methods. Determination of the prolonged toxicity of substances to freshwater fish. Method for evaluating the effects of substances on the growth rate of rainbow trout [Oncorhynchus mykiss Walbaum (Teleostei, Salmonidae)] Part 5.17, (15th April 1995) - British Standards Institution,
No abstract available